Lampranthus alboroseus (Ruschioideae, Aizoaceae), a new species from the mountains of the Western Cape, South Africa - Klak, Cornelia; Helme, Nick; Bruyns, Peter V. (Phytotaxa, 2020)
A new species―Lampranthus alboroseus―is described from the summits of two mountains in the Southern Cederberg of the Western Cape Province. Florally it resembles L. antonii but differs in having a creeping and mat-forming habit and in its overall smaller size. The creeping habit is shared with L. reptans which, however, develops noticeably longer pedicels.